DOI: 10.26512/2015.02.d.17901
|View full text |Cite
|
Sign up to set email alerts
|

A quem respondem os ruralistas? Base eleitoral e proposições legislativas dos deputados federais da 54a Legislatura

Abstract: The Congressional Rural Caucus in the Chamber of Deputies has grown in number and influence. Parallel to that, Brazil has continued to become less and less rural. That seeming contradiction suggests two explanations. The first one is that the rural agenda is based on the rural vote, which is overrepresented. The second one is that the rural agenda is justified by other factors external to the elections, mainly campaign financing. The current work analyses and tests these hypotheses aiming to explain what gives… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
2

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 14 publications
0
2
0
2
Order By: Relevance
“…Carvalho (2017) found no discernible impact of electoral donations from private health plan companies on the introduction of bills favorable to the sector by Brazilian deputies. Conversely, Cruz (2015( and Mancuso et al (2020, 2019 observed that federal deputies who received the most funding from agribusiness and industry, respectively, tended to legislate more in favor of these sectors.…”
Section: Agribusiness Interests and Parliamentary Behaviormentioning
confidence: 99%
See 1 more Smart Citation
“…Carvalho (2017) found no discernible impact of electoral donations from private health plan companies on the introduction of bills favorable to the sector by Brazilian deputies. Conversely, Cruz (2015( and Mancuso et al (2020, 2019 observed that federal deputies who received the most funding from agribusiness and industry, respectively, tended to legislate more in favor of these sectors.…”
Section: Agribusiness Interests and Parliamentary Behaviormentioning
confidence: 99%
“…Within the national literature, scholars such as Cruz (2015), Carvalho (2017), and Mancuso et al (2020Mancuso et al ( , 2019 have explored the correlation between electoral financing from various sectors of the business community and legislative output in the Brazilian parliament, particularly during the 54 th legislature. Carvalho (2017) found no discernible impact of electoral donations from private health plan companies on the introduction of bills favorable to the sector by Brazilian deputies.…”
Section: Agribusiness Interests and Parliamentary Behaviormentioning
confidence: 99%
“…Nesse sentido, o trabalho se aproxima mais do esforço realizado por Cruz (2015), que analisou o efeito do financiamento eleitoral concedido por empresas rurais sobre a produção legislativa dos parlamentares, e por Carvalho (2017), que avaliou o impacto do financiamento concedido por planos de saúde sobre a produção de proposições legislativas de interesse do setor. Também aqui os resultados encontrados foram contraditórios.…”
Section: Introdução E Discussão Com a Literaturaunclassified
“…A bibliografia especializada na análise dos grandes proprietários de terra privilegia a representação patronal e suas entidades em contextos nacional (Bruno, 1997(Bruno, , 2009Mendonça, 2009) ou regionais (Heinz, 1991;Gasparotto, 2016;Costa, 2019), sua ação política em momentos de tensões sociais e grandes disputas (Da Ros, 2012), a atuação destes grupos no parlamento, de modo especial pela chamada bancada ruralista (Vigna, 2007;Cruz, 2015;Carneiro, 2020; dentre outros), sua relação com a agricultura familiar (Bruno, 2016;Sauer, 2008), com o tema ambiental e com comunidades e povos tradicionais (Bruno, 2017;Rauber, 2021), a construção de trajetórias de grupos específicos e o acúmulo de capitais cultural, simbólico e social (Grijó, 1998;Piccin, 2015) e a formação política do agronegócio ao longo do tempo (Pompeia, 2021). Mas poucos são os trabalhos que se dedicam a analisar a construção das identidades e representações sociais do patronato rural, tendo em vista as mobilizações agenciadas por eles, com destaque para Carneiro (2008) e Da Ros (2009.…”
unclassified